User satisfaction survey in the Faculty of Humanities and Social Sciences Library – do we manage to deliver? (Libellarium: journal for research in the field of information and related sciences, 2016)
Faculty of Humanities and Social Sciences Library in Osijek has demonstrated through its activities and emphasized in its strategic documents that it is focused on the continuous improvement of its quality. In connection with this focus, the library has decided to conduct a regular triennial user satisfaction survey. This paper presents the comparative results of the two user satisfaction surveys conducted in the academic years 2009/2010 and 2012/2013. The results show to what degree the library manages to maintain the level of user satisfaction.
Keywords: Faculty of Humanities and Social Sciences; user satisfaction survey; performance quality; academic libraries